WeCWI Integrated Solutions (WeCWIIS): design to innovate! / Assoc. Prof. Ts. Dr. Mah Boon Yih - Mah, Boon Yih (Academy of Language Studies, 2022)
WeCWI Integrated Solutions (WeCWIIS) is a web-based solution-driven consultancy accessible at https://www.wecwi.com, which is founded on Web-based Cognitive Writing Instruction (WeCWI), an award-winning hybrid e-framework for instructional design and language development. WeCWIIS was established on January 1, 2020, by Assoc. Prof. Ts. Dr. Mah Boon Yih, the founder of WeCWI. Furthermore, WeCWIIS is the result of technopreneurship, which is the combination of WeCWI and entrepreneurship aimed at commercialising innovation and research to support the objectives of the Business Innovation & Technology Commercialization Centre (BITCOM), Universiti Teknologi MARA (UiTM). Consulting services, professional courses, academic resources, news advertising, and membership subscriptions are all available through WeCWIIS. Skills development, editing, translating, and proofreading, as well as research advice and cooperation, are all part of the consulting services. English language skills, postgraduate studies, and instructional technology are among the professional courses available. Open-access academic materials on WeCWI, e-learning, language, innovation, Microsoft, and postgraduate concerns are available through blog postings, research articles, a YouTube channel, and a Flipboard magazine. Furthermore, sponsors are invited to publicise and promote their academic-related news, events, or programmes on the News channel for a fee of RM10 each day. If you are interested, please fill out the Contact form at https://www.wecwi.com/post/wecwiis.